Cervical musculoskeletal impairments in the 4 phases of the migraine cycle in episodic migraine patients. (August 2022) - Di Antonio, Stefano; Arendt-Nielsen, Lars; Ponzano, Marta; Bovis, Francesca; Torelli, Paola; Finocchi, Cinzia; Castaldo, Matteo
Objective: To assess cervical musculoskeletal impairments during the 4 phases of a migraine cycle in episodic migraine patients, controlling for the presence of concomitant neck pain. Methods: Differences in cervical musculoskeletal impairments were assessed during the 4 migraine phases in episodic migraine patients and compared with healthy controls controlling for concomitant neck pain. Cervical musculoskeletal impairments were assessed as follow: cervical active range of motion; flexion rotation test; craniocervical flexion test and calculation of activation pressure score; the total number of myofascial trigger points in head/neck muscles; the number of positivevertebral segments (headache's reproduction) during passive accessory intervertebral movement; pressure pain thresholds over C1, C2, C4, C6 vertebral segments bilaterally, trigeminal area, hand, and leg. Signs of pain sensitization were assessed by evaluating mechanical pain threshold over trigeminal area and hand, pressure pain thresholds, and the wind-up ratio. The Bonferroni-corrected p-value (05/4 = 0.013) was adopted to assess the difference between groups, while a p-value of 0.05 was considered significant for the correlation analysis. Results: A total of 159 patients and 52 controls were included. Flexion rotation test and craniocervical flexion test were reduced in all 4 phases of the migraine cycle versus healthy controls (p < 0.001). The number of myofascial trigger points and positive vertebral segments was increased in all 4 phases of the migraine cycle versus healthy controls (p < 0.001). Flexion, extension, and total cervical active range of motion and cervical pressure pain thresholds were reduced in episodic migraine in the ictal phase versus controls (p < 0.007) with no other significant differences. Outside the ictal phase, the total cervical active range of motion was positively correlated with trigeminal and leg pressure pain threshold (p < 0.026), the number of active myofascial trigger points and positive positive vertebral segments were positively correlated with higher headache frequency (p=0.045), longer headache duration (p < 0.008), and with headache-related disability (p = 0.031). Cervical pressure pain thresholds were positively correlated with trigeminal, hand, and leg pressure pain threshold (p < 0.001), and trigeminal and leg mechanical pain thresholds (p < 0.005), and negatively correlated with the wind-up ratio (p < 0.004). Conclusion: In all phases of the migraine cycle, independent of the presence of concomitant neck pain, episodic migraine patients showed reduced flexion rotation test and craniocervical flexion test and an increased number of myofascial trigger points and passive accessory vertebral segments. These impairments are correlated with enhanced headache duration, headache-related disability, and signs of widespread pain sensitization. Reduction in active cervical movement and increased mechanical hyperalgesia of the cervical was consistent in ictal episodic migraine patients and the subgroups of episodic migraine patients with more pronounced widespread sensitization.